AN EVALUATION OF THE ADEQUACY OF THE AFRICAN CHARTER ON THE RIGHTS OF THE CHILD CONCERNING ECONOMIC CRIMES IN ARMED CONFLICT - Nanima, Robert D (Journal of Anti-Corruption Law, 2023)
Statistics indicate that at least one in every four African children lives in a conflict zone. Six of the ten worst countries for children to grow up in, or live in, are in Africa: the Central African Republic, the Democratic Republic of Congo, Mali, Nigeria, Somalia and South Sudan. It is widely observed that economic crimes continue to disrupt the political, social and economic fabric of society. This is exacerbated where there is armed conflict and armed groups continue to use children as a tool to benefit them through illegal acts that lead to financial advantages.